2021
DOI: 10.1186/s12886-021-01928-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ocular biometric variations after scleral buckling surgery in macula-on rhegmatogenous retinal detachment

Abstract: Background Myopic shift and biometric ocular changes have been previously observed after scleral buckling (SB) surgery in rhegmatogenous retinal detachment (RRD), but long term-term outcomes had not yet been explored. The purpose of present study is to evaluate long term ocular biometric changes in patients with primary macula-on RRD treated with SB. Methods In this retrospective, observational study, we reviewed the medical records of patients und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
4
1
1
Order By: Relevance
“…[6] evaluated the ACD by AS-OCT and found a signi cant decrease until 9 months after SB surgery. Similarly, the ACD decrease after scleral encircling has been attributed to the anterior rotation of the ciliary body associated with surgicallyinduced ciliary congestion and subsequent forward shift of the lens-iris diaphragm [17]. However, in our study, there was no signi cant decrease of the CACD in the operated eyes.…”
Section: Discussioncontrasting
confidence: 52%
“…[6] evaluated the ACD by AS-OCT and found a signi cant decrease until 9 months after SB surgery. Similarly, the ACD decrease after scleral encircling has been attributed to the anterior rotation of the ciliary body associated with surgicallyinduced ciliary congestion and subsequent forward shift of the lens-iris diaphragm [17]. However, in our study, there was no signi cant decrease of the CACD in the operated eyes.…”
Section: Discussioncontrasting
confidence: 52%
“…Although ACD was still significantly deeper and AL was longer at the final follow-up visit than at baseline, despite having a myopic shift, SER revealed no significant difference from baseline values in our participants. In contrast, Albanese et al [ 22 ] found a significant myopic shift at the last follow-up in operated eyes compared to baseline refraction. Despite the differences in the phakic status of the included eyes and the study design, using an absorbable suture to tighten the encircling band resulted in the reduced significance of the myopic shift in our study.…”
Section: Discussionmentioning
confidence: 90%
“…Albanese et al [ 22 ] found significant differences in AL, ACD, and SER in phakic eyes treated with SB for primary macula-on RRD compared with fellow phakic eyes at a mean (SD) follow-up duration of 50.9 (21.9) months. Operated eyes experienced -1.35 (0.57) D myopic shift, 0.83 (0.23) mm increase in mean (SD) AL, and 0.09 (0.18) mm shallowing in mean (SD) ACD at the last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…28 Scleral buckling surgery alters the ocular structure, resulting in a longer AL and shallower ACD compared with preoperative measurements. [29][30][31] These changes in turn affect the IOL calculation, but the prediction accuracy for such patients remains largely unknown. Lamson et al observed a myopic bias (À0.159 D) in eyes with previous scleral buckling, whereas the difference was not statistically significant when compared with the total population.…”
Section: Discussionmentioning
confidence: 99%